볼로미터형 적외선 센서의 신호처리회로 설계 및 특성 - 김진수; 박민영; 노호섭; 이승훈; 이제원; 문성욱; 송한정 (한국센서학회, 2007)
×32 infrared focal plane array (IRFPA) detector, whichconsist of reference resistor, detector resistor, reset switch, integrated capacitor and operational amplifier. Proposed ROICis designed using 0.35m 2P-4M (double poly four metal) n-well CMOS process parameters. Low noise folded cascodeoperational amplifier which is a key element in the ROIC showed 12.8 MHz unity-gain bandwidth and open-gain 89 dB,phase margin 67o, SNR 82 dB. From proposed circuit, we gained output voltage variation 17 mV/oC when the detectorresistor varied according to the temperature.